Teknologi Pembuatan Material Shot Blast untuk Mendukung Industri Pengecoran Logam Nasional - Fajar Nurjaman (Institute of Research and Community Outreach, Petra Christian University, 2009)
Shot blast material is a supporting material in foundry which is used at surface finishing process of metal casting. Recently, there is no one of national industry that produce shot blast material, in consequence, the purpose of this research is to lessen the dependence of using shot blast material import by making a shot blast material which improve its hardness exceed the shot blast material import. This research use the raw material from scrap iron with the following composition: C (3.2%), Si (1.18%), Mn (6.1%), Cu (0.35%), Fe (88.7%). The scrap is melted in induction furnace untill melt (hot metal), then the hot metal (1200 oC) is tilted into a runner which is connected with pan crucible, which is consisted of 107 holes with diameter of each holes is 10 mm. Hot metal that is leave from the holes, is injected by pressurized water 1.1 atm with the velocity 0.8 m/s, untill obtained grains of shot blast material, then these grains goes into the water tank which it has temperature 40oC. From thermodynamic study, to avoid the happening of the explosion that is arising out because the effect of high temperature difference at injection process beetween water and hot metal, hence the comparison value beetween the mass of water and hot metal equal to 1:4.6. From this research is obtained shot blast material Ø0.8-3.2 mm with the metallography structure with martensite domination and dispersion of cementite and a little austenit. The hardness value of this material is 54.8 HRC, where this value is larger than shot blast material import (45-50 HRC). Abstract in Bahasa Indonesia: Material shot blast merupakan material pendukung pengecoran logam yang digunakan pada proses surface finishing benda cor logam. Saat ini belum ada satupun industri nasional yang memproduksi material shot blast, karena itu tujuan penelitian ini untuk mengurangi ketergantungan penggunaan material shot blast impor dengan membuat material shot blast yang nilai kekerasannya melebihi material shot blast impor. Penelitian ini menggunakan bahan baku scrap besi dengan komposisi: C (3,2%), Si (1,18%), Mn (6,1%), Cu (0,35%) Fe (88,7%). Scrap dilebur dalam tungku induksi hingga mencair (hot metal), lalu hot metal (1200oC) di tuang ke dalam runner yang terhubung dengan pan crucible yang terdiri dari 107 buah lubang berukuran Ø10 mm. Hot metal yang keluar dari lubang tersebut diinjeksi oleh air bertekanan 1,1 atm dengan kecepatan 0,8 m/s, hingga diperoleh butiran material shot blast, lalu butiran itu masuk ke dalam bak air bertemperatur 40oC. Dari kajian termodinamika, untuk menghindari terjadinya resiko ledakan yang timbul akibat diferensiasi temperatur yang tinggi saat proses injeksi, maka besarnya nilai perbandingan massa air dan hot metal sebesar 1:4,6. Dari penelitian ini diperoleh material shot blast berukuran Ø0,8-3.2 mm dengan struktur metalografi yang didominasi oleh struktur martensit dengan sebaran sementit dan sedikit austenit. Nilai kekerasan material ini adalah 54,8 HRC, dimana nilai ini melebihi nilai kekerasan material shot blast impor (45-50 HRC). Kata kunci: Shot blast, induction furnace, nozzle, hot metal, pengecoran logam.